Karakteristik Geologi Daerah Dambalo dan Sekitarnya Kabupaten Gorontalo Utara, Provinsi Gorontalo - Ismail, Zenza Harnold; Permana, Aang Panji; Zainuri, Ahmad (Universitas Negeri Gorontalo, 2024)
Dambalo is a village located in Tomilito sub-district, North Gorontalo Regency, Gorontalo Province. This study aims to identify and describe the geological characteristics of the Dambalo area and its surroundings. The study focuses on geomorphology, stratigraphy, geological structure, and geological potential. The methods used include field observation and laboratory analysis. Field observations include geological mapping, rock sampling, and measuring geological structures using a geological compass. Meanwhile, laboratory analysis was carried out to determine the mineral composition, rock texture and rock name through petrography and stratigraphic analysis. The results of the study indicate that the study area is stratigraphically composed of the oldest to the youngest lithological units, namely porphyry andesite units, volcanic breccias, and alluvial deposits. The dominant geological structure is tensile fractures (tension fractures) with three main orientations. The geological potential in this area includes C-type mining materials, which mainly consist of porphyry andesite rocks, which have economic value for the construction industry. However, this area also has the potential for landslide hazards, namely in areas with steep slopes. This research is expected to contribute to the management of natural resources and mitigation of geological landslide disasters in Dambalo and its surroundings.